Standardisation of nailfold capillaroscopy for the assessment of patients with Raynaud's phenomenon and systemic sclerosis - Smith, Vanessa (2020)
Capillaroscopy is a non-invasive and safe tool which allows the evaluation of the morphology of the microcirculation. Since its recent incorporation in the 2013 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria for systemic sclerosis together with its assessed role to monitor disease progression, capillaroscopy became a ‘mainstream’ investigation for rheumatologists. Given its increasing use by a variety of physicians internationally both in daily practice to differentiate primary from secondary Raynaud's phenomenon, as well as in research context to predict disease progression and monitor treatment effects, standardisation in capillaroscopic image acquisition and analysis seems paramount. To step forward to this need, experts in the field of capillaroscopy/microcirculation provide in this very consensus paper their view on image acquisition and analysis, different capillaroscopic techniques, normal and abnormal capillaroscopic characteristics and their meaning, scoring systems and reliability of image acquisition and interpretation.